Continuity and change in grammar - Breitbarth, Anne, 1976- (Linguistik aktuell ;, 2010)
One of the principal challenges of historical linguistics is to explain the causes of language change. Any such explanation, however, must also address the 'actuation problem': why is it that changes occurring in a given language at a certain time cannot be reliably predicted to recur in other languages, under apparently similar conditions? The sixteen contributions to the present volume each aim to elucidate various aspects of this problem, including: What processes can be identified as the drivers of change? How central are syntax-external (phonological, lexical or contact-based) factors in.